A novel piwi-interacting RNA associates with type 2–high asthma phenotypes - Li, Jiang; Hong, Xiaoning; Jiang, Mingye; Kho, Alvin T.; Tiwari, Anshul; Wang, Alberta L.; Chase, Robert P.; Celedón, Juan C.; Weiss, Scott T.; McGeachie, Michael J.; Tantisira, Kelan G. (Journal of allergy and clinical immunology, 2024)
[Display omitted] Piwi-interacting RNAs (piRNAs), comprising the largest noncoding RNA group, regulate transcriptional processes. Whether piRNAs are associated with type 2 (T2)-high asthma is unknown. We sought to investigate the association between piRNAs and T2-high asthma in childhood asthma. We sequenced plasma samples from 462 subjects in the Childhood Asthma Management Program (CAMP) as the discovery cohort and 1165 subjects in the Genetics of Asthma in Costa Rica Study (GACRS) as a replication cohort. Sequencing reads were filtered first, and piRNA reads were annotated and normalized. Linear regression was used for the association analysis of piRNAs and peripheral blood eosinophil count, total serum IgE level, and long-term asthma exacerbation in children with asthma. Mediation analysis was performed to investigate the effect direction. We then ascertained if the circulating piRNAs were present in asthmatic airway epithelial cells in a Gene Expression Omnibus (GEO; www.ncbi.nlm.nih.gov/geo) public data set. Fifteen piRNAs were significantly associated with eosinophil count in CAMP (P ≤ .05), and 3 were successfully replicated in GACRS. Eleven piRNAs were associated with total IgE in CAMP, and one of these was replicated in GACRS. All 22 significant piRNAs were identified in epithelial cells in vitro, and 6 of these were differentially expressed between subjects with asthma and healthy controls. Fourteen piRNAs were associated with long-term asthma exacerbation, and effect of piRNAs on long-term asthma exacerbation are mediated through eosinophil count and serum IgE level. piRNAs are associated with peripheral blood eosinophils and total serum IgE in childhood asthma and may play important roles in T2-high asthma.